Comparative Biochemical Composition of Natural and Fattened Mud Crab Scylla serrata (Journal of Scientific Research, 2013)
The biochemical composition (proteins, lipid, ash and moisture) of different parts of the body (gill, meat, egg) of fattened and natural mud crab Scylla serrata was determined. Twenty four samples of S. serrata (12 from wild & 12 from fattening farm) of different sizes and sexes (half of the sample is male) were used in this study. The mean protein and lipid contents are significantly (p